Die Landschaft Bukowina Das Werden einer Region an der Peripherie 1774-1918 - Scharr, Kurt (2010)
Bucovina was an integral part of Habsburg Empire since 1775. Starting from a pure political construction on the European map of power at the end of 18th century this small area developed into a well integrated Austrian crown land. A crown land, which succeeded to form a certain regional identity - conform to the Habsburg state ideology. Till the outbreak of First World War national rivalries played a certain role for regional politics in the county but were moderate in general. Especially this situation was grounded in a direct liaison of this small province situated on the Eastern slopes of Carpathians with Vienna as imperial centre. A development which aimed towards steadily improving inner consolidation and balance in comparison with the other crown lands of the Empire. Only the outcome of the First World War, as Bucovina became part of the Romanian kingdom, loosing its geo strategic position as a bridge between East and West, showed in its consequences the former importance of this organic exchange with Vienna, shaping the provinces society and cultural landscape. The genesis of Bucovina region at the periphery of a European Empire from the end of 18th up to the beginning of 20th century as well as the structural persistence of the cultural landscape's characteristics is centrally focussed in this study. The analyses of spatial processes as well as their genesis, shaped by a changing geopolitical situation, were of main interest for the research. Since the midst of 19th century a serious and existential national tension within the Bucovina was growing which could only partially be influenced by the province politics itself. A tension in between a search for a distinguished political position, the new idea of nation state and a overall-covering ideology of Commonness, a tension between growing regional identity, of beeing Bucovina and increasing national claims. The study tries to draw a knew, integral and less known picture of this variously shaped cultural landscape - apart from common nationalistic and segmented analyses.